The influence of hybrid personal interaction and authentic content on customer emotional connection at bt batik trusmi cirebon - Pandu Pramudya Raka Pratama; Siska Ernawati Fatimah (Institute of Computer Science (IOCS), 2026)
This research sought to examine the influence of Hybrid Personal Interaction and Authentic Content on Customer Emotional Connection at BT Batik Trusmi Cirebon. The increasing integration of offline and digital channels has shifted customer interactions toward a hybrid experience, requiring firms to manage both service encounters and content authenticity simultaneously to maintain psychological bonds. A quantitative method utilizing a causal design was employed, involving 180 respondents selected via purposive sampling who had experienced both physical store visits and digital interactions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings showed that the model had strong explanatory power, with an R2 value of 0.687, meaning that Hybrid Personal Interaction and Authentic Content jointly explained 68.7% of the variance in Emotional Connection. Hybrid Personal Interaction demonstrated a powerful and noteworthy beneficial impact on Emotional Connection (b = 0.792, p < 0.05), making it the dominant predictor. Meanwhile, Authentic Content also had a positive and significant effect (b = 0.094, p < 0.05), although its contribution was relatively smaller. These findings suggested that emotional connections in heritage retail are primarily driven by responsive and empathetic service interactions across hybrid channels, while authentic content strengthens cultural value. This research adds to the relationship marketing literature by incorporating hybridity and authenticity in an omnichannel context